Influence of Exposure to Different Green Rooftop Spaces on Stress Restoration of College Students - Zhixiong ZHUO; Liang DONG (Fengjing Yuanlin)
ObjectiveAlong with the continuous progress of urbanization, the number of people living in cities is increasing. Although urbanization can offer people many conveniences, a large number of people also face different degrees of health risks in their daily lives, such as the increasing spread of various diseases, the growing prominence of psychological problems and the increasing health risks in cities. With aggravated social competition, college students are prone to physical and psychological health problems when facing academic tasks. Therefore, students are in urgent need of healing pathways to relieve their physical and psychological stress. The healing function of the natural environment is becoming more and more prominent. Exposure to the natural environment can reduce the stimulation of stressors from daily life and alleviate people’s psychological and physiological stress. Urban green spaces, which are mainly natural environments, have been explored for their health restoration benefits, and in recent years green rooftops have also been noted for their potential to promote physical and psychological health. As a new form of urban green space, green rooftops have certain ecological service values, such as the reduction of building energy consumption, the management of stormwater and the mitigation of heat island effect. Although green rooftops have limited space, their natural elements provide people with opportunities to engage with nature and gain restorative experience, making them important places to promote healthy and sustainable human settlement environments. Therefore, this research explores the influence of exposure to green rooftop space on the physical and psychological restoration of college students from both physiological and psychological perspectives through a field experiment.MethodsIn order to determine the restorative effects of green rooftops on physical and psychological health, three types of green rooftop spaces (water space, wooden plaza, and ecological sunroom) and a control group (non-green rooftop space) in the Experimental Building of Architecture Discipline of Huaqiao University are selected to explore the restorative potentials of green rooftop space. Field measurements are conducted during the daytime on a sunny and windless day, with no significant difference between the physical environments of different green rooftop spaces. 35 college student volunteers participate in the experiment, all of whom are daily users of green rooftop space. The volunteers are in good health without any adverse symptoms, who are asked to eat a healthy diet and get enough sleep before the experiment. The research adopts a within-subjects design to quantitatively analyze the influence of exposure to green rooftop space on the physiological and psychological health indicators of college students by using biofeedback (blood pressure and heart rate variability) and psychological state (brief profile of mood states) measures. The research uses SPSS 26.0 software to process all data.Results1) Compared to non-green rooftop space, both psychological and physiological indicators show positive improvement in green rooftop space. Specifically, the values of tension, anger, fatigue, confusion, depression and TMD in the emotional factors decrease significantly, while the values of vitality increase significantly after exposure to green rooftop spaces. TMD decreases significantly in green rooftop space compared to non-green rooftop space, suggesting that exposure to green rooftop space can suppress negative emotions, promote positive emotions, and provide pleasant sensory stimulation for college students. Positive changes in physiological indicators further explain that green rooftop space has health restoration effects. Compared with the changes in physiological indicators, the changes in psychological indicators are more significant. 2) The three green rooftop spaces have different degrees of health restoration benefits, and the mood factor TMD reveals that the water space performs best in stress restoration, followed by the seco-sunroom and the wooden plaza. Positive changes in all physiological indicators also occur in the water space, with only a significant decrease in systolic blood pressure in the ecological sunroom, and no significant changes in all physiological indicators in the wooden plaza. Overall, in terms of health restoration benefits, the three green rooftop spaces rank in the order of water space, ecological sunroom and wooden plaza from high to low. 3) There exist significant correlations between the values of changes in some psychological and physiological indicators, among which the physiological indicators diastolic blood pressure and LF/HF are significantly correlated with the values of fatigue and depression in the mood factor, respectively.ConclusionThrough scientific field measurements of the influence of green rooftop space on stress restoration of college students, the research finds that green rooftop space has a supportive role in the restoration of physical and psychological health of college students. The restorative benefits of different green rooftop spaces differ significantly, with more naturalized green rooftop spaces showing better stress restoration benefits. The results of the research may help improve people’s awareness of the restorative value of green rooftop space, further support the argument that green rooftop space promotes physical and psychological health, and provide a theoretical basis for the design of green rooftop space based on the healthy concept.